Resistance-curve envelopes for dental lithium disilicate glass-ceramics. Issue 5 (May 2022) - Lubauer, Julia; Ast, Johannes; Göken, Mathias; Merle, Benoit; Lohbauer, Ulrich; Belli, Renan
Highlights: Here we confirm indications that lithium disilicates for dental applications show R-curve behaviour. We provide the shape of the R-curve for three different microstructures, with random or aligned Li2 Si2 O5 crystals. The initial value of the R-curve was obtained using a 1.4 μm long notch of 20 nm radius in a micro-cantilever specimens prepared by focused-ion-beam milling. Abstract: Recent investigations on the mechanics of dental lithium disilicates have gathered mounting evidences of a probable R-curve behavior. Here we use an indirect approach to obtain the contours of the R-curve using the relationship between strength and initial crack size obtained from quasi-static fracture toughness tests. The tangent condition formed by the multiple K I, appl ( a i, j ) curves give a smoothened polygonal envelope for the R-curves. The R-curves obtained this way were extended toward an initial value at the onset of stable crack extension, obtained hereusing a microcantilever specimen featuring a sharp notch produced by focused-ion-beam milling. The presence of an R-curve effect was confirmed for the three evaluated lithium disilicates, being more pronounced for the injection-molded material having an oriented elongated Li2 Si2 O5 microstructural architecture, with crystal fraction playing an important role for low-aspect ratio randomly-oriented microstructures.